Short peptides derived from the NH2-terminus of subclass IIa bacteriocin enterocin CRL35 show antimicrobial activity - Salvucci, Emiliano Jesus (2007)
Objectives: Subclass IIa bacteriocins are characterized by a hydrophilic N-terminal domain that shares a YGNGVxCxxxxC consensus and a variable hydrophobic C-terminus. Enterocin CRL35 is a 43- amino-acid heat stable peptide with antilisterial activity. Short synthetic peptides derived from the N-terminal half of enterocin CRL35 and other subclass IIa bacteriocins were evaluated for antimicrobial properties. Methods: In vitro activities of synthetic peptides were evaluated in complex, chemically defined and minimal media. MIC assays were performed by the agar well-diffusion method. Fluorescence assays to evaluate the dissipation of membrane potentials in intact cells were carried out. Time-kill kinetics of Listeria innocua cells with the active peptide were performed. Results and conclusions: A 15-mer peptide derived from enterocin CRL35 inhibited the growth of L. innocua and Listeria monocytogenes in synthetic/minimal media and dissipated the membrane potential of sensitive cells, with MICs of 10 and 50 mM, respectively. 15-mer derivatives from other class IIa bacteriocins (mesentericin Y105, pediocin PA-1 and piscicolin 126) also showed antimicrobial activities.